Prospective Directions of Implementation of Modern Information Technologies in Education - Abdullayeva Sanobar Berdiyevna; Xujakulov Shaxriyor Shokirovich (Genius Journals, 2023)
Today, in the education system of our republic, the technology of using new information technologies, including electronic and distance education, as well as electronic educational methodical complexes, is considered the demand of the time. One of the main directions of the process of informatization of the current society is the informatization of education. Today's task of education is to teach students to be able to work independently in the conditions of information-educational environment, which is improving day by day, to use the flow of information wisely. This article discusses the same issues. The article provides insights into the use of new information technologies in educational institutions.
Keywords: New modern technologies; computer; modeling; internet